2018
DOI: 10.1097/wco.0000000000000522
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and ischemic stroke: a practical guide to management

Abstract: The risk of ischemic stroke is elevated especially from the third trimester until 6 weeks postpartum. MRI is the most accurate and well tolerated diagnostic option but low-dose CT-head is a valid alternative. Reperfusion therapies should not be withheld from a pregnant woman with moderate-to-severe stroke when benefits outweigh the risk. Aspirin up to 150 mg daily is considered well tolerated during pregnancy and lactation period. Multidisciplinary care is essential when counseling these women in the acute and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 64 publications
2
39
0
Order By: Relevance
“…Although considered a somewhat scarce occurrence, ischemic strokes associated with pregnancy carry higher mortality rates. The risk is at its highest from the third trimester until 6 weeks postpartum [9]. In countries like India and Mexico, pregnancy-related stroke is not that uncommon and is caused by dural sinus thrombosis [10].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Although considered a somewhat scarce occurrence, ischemic strokes associated with pregnancy carry higher mortality rates. The risk is at its highest from the third trimester until 6 weeks postpartum [9]. In countries like India and Mexico, pregnancy-related stroke is not that uncommon and is caused by dural sinus thrombosis [10].…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, the findings in the study should be interpreted with caution due to the small number of outcome events in subgroups [ 34 ]. Although evidence is insufficient to make clear evidence-based recommendations about stroke prevention in pregnant women, Mayte et al summarized a practical guide to manage ischemic stroke during pregnancy, and suggested that aspirin (50–150 mg/day), which is well-tolerated during pregnancy, could be considered for women with higher risk of stroke, including cardioembolism, migraine, and coagulation disorders [ 35 ].…”
Section: Aspirin In Pregnancymentioning
confidence: 99%
“…Detailed laboratory evaluation to identify possible triggering causes of the disease is also important to be performed. Pregnant patients should receive individualized treatment to ensure mother and fetus' safety [1,8], including careful evaluation of the pregnant women at the beginning of prenatal care through anamnesis, obstetric history investigation and possible previous comorbidities since these factors can be aggravated by the pregnancy cycle and lead to unfavorable outcomes [8]. Authors in the current study have herein reported two clinical cases of patients who underwent stroke episodes, one before pregnancy and the other one in the first semester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%